1993
DOI: 10.1039/ft9938900081
|View full text |Cite
|
Sign up to set email alerts
|

Excess heat capacities of mixtures of two alcohols

Abstract: The molar excess heat capacity ( C i ) has been obtained through the concentration range at 25°C for mixtures of alkan-1-01s: methanol with butanol, hexanol and decanol and decanol with butanol and hexanol. C i is negative and small, increasing in magnitude with difference in chain length of the alkan-1-01s to a maximum of -3 J mol-' K-' for methanol-decanol. C i has also been measured at 25°C for methanol and other alkanols mixed with iso-, sec-and tert-butyl alcohol (I), 2-methylbutan-2-01 (ll), 3-methylpent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…Simultaneously, the minimum values of the C E p;m are correlated with the magnitude of the C p,m values of the pure butanols and the minima are in the order: 1-butanol < i-butanol < s-butanol < t-butanol [9]. Moreover, the negative values of C E p;m have been also found to exist for the other (1-alkanol + 1-alkanol) systems [7,8]. It must be pointed out here, that (1-alkanol + tertiary alcohols) systems show generally considerably more complicated composition dependence of C E p;m , i.e., s-shaped or w-shaped [8,10].…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…Simultaneously, the minimum values of the C E p;m are correlated with the magnitude of the C p,m values of the pure butanols and the minima are in the order: 1-butanol < i-butanol < s-butanol < t-butanol [9]. Moreover, the negative values of C E p;m have been also found to exist for the other (1-alkanol + 1-alkanol) systems [7,8]. It must be pointed out here, that (1-alkanol + tertiary alcohols) systems show generally considerably more complicated composition dependence of C E p;m , i.e., s-shaped or w-shaped [8,10].…”
Section: Resultsmentioning
confidence: 74%
“…In this case, the equimolar value is ca. 0.4 J AE K À1 AE mol À1 [8]. It is also interesting to note that the C E p;m values for the four systems of (methanol + isomeric butanol) are negative and show a simple concentration dependence.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In these cases, the equimolar values are À1.41 J AE K À1 AE mol À1 and ca. À0.4 J AE K À1 AE mol À1 , respectively [26,27]. It is also interesting to note that C E p;m values for the all four systems of (methanol + isomeric butanol) are negative and show a simple concentration dependence.…”
Section: Resultsmentioning
confidence: 95%
“…Accordingly, these higher alcohols cannot accept proton from CMOH. Yao et al made similar suggestions (25). It is suggested that with increasing steric crowding in the neighborhood of the hydroxyl group, hydrogen bonding interaction will be substantially weakened.…”
Section: Steady State Absorption and Emission Spectramentioning
confidence: 81%